Luxurious citizens : the politics of consumption in nineteenth-century America - Cohen, Joanna (Professor) (America in the nineteenth century., 2017)
'Luxurious Citizens' traces the ways in which Americans tied consumer desire to the national interest between 1789 and 1865 and reveals how the nation transformed individual desires for goods into an index of civic worth, placing unbridled consumption at the heart of their modern political economy.